Risks of Synovial Sepsis Following Intrasynovial Medication in Ambulatory Practice, 2006–2011: 9456 Intrasynovial Injections. (9th September 2013) - Smith, L.; Palmer, L.; Shepherd, M.; Steven, W.N.; Dallas, R.; Baldwin, G.; Sommerville, G.; Hawthorne, T.; Ramzan, P.
Abstract : Aims: To determine the incidence of synovial sepsis following intra‐articular and intrathecal injections. Synovial sepsis is a serious potential complication of intrasynovial medication. Methods: Available case records for all horses receiving intrasynovial medications (ISMs) performed by 9 ambulatory clinicians were examined over 5 years (2006–2011). Intrasynovial medications were defined as therapeutic interventions, based on clinical history and orthopaedic examination; nontherapeutic injections for diagnostic analgesia were excluded. Routine protocol was not to clip injection sites; the skin was prepared using standard aseptic technique. Scrupulous aseptic injection technique was employed at all times. All horses were under the care of a single practice, dealing with mainly Thoroughbred racehorses. Records were cross‐referenced against synovial cytology submissions and hospital admissions for synovial sepsis. Development of 2 out of 4 clinicopathological signs of synovial sepsis (lameness, joint distension, synovial white blood cell count >10, 000/l, synovial total protein >25 g/l) within 8 weeks of medication of the same synovial space was considered to represent a post medication complication (PMC). Failure of the PMC to resolve with conservative therapy was considered to represent post medication synovial sepsis (PMSS). Results: During the study period 9456 ISMs were recorded, in 4332 sessions, in 1732 horses. Corticosteroids were included in 92.3% of ISMs, 94.8% included amikacin and 0.15% (14/9456) included polysulphated glycosaminoglycans (PSGAGs). Twelve horses developed PMC (0.0013% ISM), 4 horses developed PMSS (0.0004% ISM). All 4 horses returned to use following joint lavage. Administration of intrasynovial PSGAGs, was significantly associated with PMSS (P<0.0001 OR = 787 95% CI 145–20, 337). Intrasynovial medications that included amikacin were less likely to develop PSSM (P = 0.005 OR = 0.0181 95% CI 0.0019–0.174); however if the PSGAGs group was excluded the difference became nonsignificant (P = 0.0981). Conclusions and practical significance: The risk of iatrogenic sepsis following intrasynovial medication is extremely low. Intrasynovial medication with PSGAGs should be avoided without concomitant antimicrobials. Acknowledgements: A. Wilson and K. Batteate for case collation. Ethical animal research: Not required by this Congress: retrospective analysis of case records.Sources of funding: None.Competing interests: None.